2014
DOI: 10.3109/0886022x.2014.918785
|View full text |Cite
|
Sign up to set email alerts
|

Safety of total dose iron dextran infusion in geriatric patients with chronic kidney disease and iron deficiency anemia

Abstract: There are limited data on total dose infusion (TDI) using iron dextran in geriatric chronic kidney disease (CKD) patients with iron-deficiency anemia (IDA). Our goal was to evaluate the safety of TDI in this setting. We conducted a retrospective chart review spanning a 5 year period (2002-2007), including all patients with CKD and IDA who were treated with iron dextran TDI. Patient demographics were noted, and laboratory values for creatinine, hemoglobin and iron stores were recorded pre- and post-dose. TDI di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…iron as FCM. These findings compare favourably with data published recently by Dossabhoy et al [ 28 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…iron as FCM. These findings compare favourably with data published recently by Dossabhoy et al [ 28 ].…”
Section: Discussionsupporting
confidence: 92%
“…While safety data for i.v. iron supplementation in geriatric patients are scarce, a recent retrospective study by Dossabhoy demonstrated iron dextran to be relatively safe and effective in elderly patients (mean, 70 years) with chronic kidney disease [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar particles, for example, iron-carbohydrate solutions or iron-dextran, have been used in humans for anemia treatment with a good safety profile. 29,30 We could show that these "untouched" Treg cells are also functional as they were able to suppress proliferation of autologous CD4 Teff cells. The degree of suppressive capacity showed considerable variability; this is not necessarily exclusively due to quantitative variations in the functional status of the Treg cells.…”
Section: Discussionmentioning
confidence: 96%
“…Finally, it is worth mentioning the use of dextran-hemoglobin conjugates as blood substitutes for patients suffering from asthma or other hemoglobin-compromised conditions. These dextran derivatives not only increase the therapeutic efficiency by enhancing the binding and release of oxygen [111][112][113][114], but also prevent hemoglobin excretion (avoiding any kidney damage [115,116]), reduce the non-renal clearance of hemoglobin (therefore minimizing risks of tissue edema [117]) and reduce the auto-oxidation described for other hemoglobin-based oxygen carriers (reducing tissue and cellular toxicity [118]).…”
Section: Dextranmentioning
confidence: 99%